Finite element analysis of Puddu and Tomofix plate fixation for open wedge high tibial osteotomy - Raja Izaham, R.M.A.; Abdul Kadir, M.R.; Abdul Rashid, A.H.; Hossain, M.G.; Kamarul, Tunku (2012)
The use of open wedge high tibial osteotomy (HTO) to correct varus deformity of the knee is well established. However, the stability of the various implants used in this procedure has not been previously demonstrated. In this study, the two most common types of plates were analysed (1) the Puddu plates that use the dynamic compression plate (DCP) concept, and (2) the Tomofix plate that uses the locking compression plate (LCP) concept. Three dimensional model of the tibia was reconstructed from computed tomography images obtained from the Medical Implant Technology Group datasets. Osteotomy and fixation models were simulated through computational processing. Simulated loading was applied at 60:40 ratios on the medial:lateral aspect during single limb stance. The model was fixed distally in all degrees of freedom. Simulated data generated from the micromotions, displacement and, implant stress were captured. At the prescribed loads, a higher displacement of 3.25 mm was observed for the Puddu plate model (p < 0.001). Coincidentally the amount of stresses subjected to this plate, 24.7 MPa, was also significantly lower (p < 0.001). There was significant negative correlation (p < 0.001) between implant stresses to that of the amount of fracture displacement which signifies a less stable fixation using Puddu plates. In conclusion, this study demonstrates that the Tomofix plate produces superior stability for bony fixation in HTO procedures.